Molecular phylogeny and morphology reveal a new species of Radulomyces (Radulomycetaceae, Agaricales) from Southwestern China - Chen, Daxiang; Zhang, Shihui; Yang, Runfen; Li, Chengjun; Yan, Maolin; Dong, Junhong; Zhao, Changlin (Phytotaxa, 2025)
Radulomyces tongbiguanensis sp. nov., discovered in Yunnan Province, southwestern China, is described here as a new species based on its morphology and phylogenetic analysis. Radulomyces tongbiguanensis is characterized by its membranaceous basidiomata, which have a smooth hymenial surface and a monomitic hyphal system bearing clamp connections on the generative hyphae, and globose basidiospores measuring 9.5–11.5 × 9–11 µm. Phylogenetic analyses of the new species were conducted based on internal transcribed spacer (ITS) and large subunit (LSU) ribosomal DNA (rDNA) sequences. The phylogenetic analysis indicated that the new species belongs to the genus Radulomyces, and is retrieved grouped with the species R. zixishanensis. However, morphologically R. zixishanensis differs from R. tongbiguanensis by cream to slightly brown basidiomata, narrower basidia (28–43 × 6.5–8.5 µm vs. 28.5–40 × 10–12.5 µm), and ellipsoid, narrower basidiospores (7–8.8 × 5.5–6.8 µm vs. 9.5–11.5 × 9–11 µm). A full description, illustrations, and phylogenetic analysis results of the new species are provided.